The use of Anti-Retroviral drugs in the Prevention of Mother to Child Transmission (PMTCT) of HIV (Tanzania Medical Journal, 2015)
Mother to child transmission is by far the main mode of transmission of HIV to the child. In an attempt to curb the situation, many interventions have been proposed and targeted at the antenatal, natal and postnatal stages. More recently, the Ministry of Health and Social Welfare developed the National PMTCT guidelines to be used and adopted throughout the country. There are several interventions that have been proposed and implemented, this papers focuses particularly on the use of antiretroviral drugs during each of these phases and outlines some technical challenges faced by the programme before achievement levels can reach those of developed nations.